Colloquial neologisms in the modern Ukrainian language - STYSHOV, Oleksandr (Ukrainian linguistics, 2024)
Background. The article is devoted to the analysis of new colloquial words that arose and function in the Ukrainian language of the 21st century. The Ukrainian language is currently characterized by significant dynamics at all its levels, and especially at the lexical-semantic level. Undoubtedly, extralingual and intralingual factors that are in constant interaction and complement each other contribute to this. A characteristic feature of the mentioned period is that colloquial neologisms became one of the important sources of replenishment of the lexical-semantic layer of the Ukrainian language. Their emergence was caused by democratization and liberalization in Ukrainian society during the analyzed period, which significantly affected the language, in particular, expanded the boundaries of its functioning. The material for this studio was primarily new colloquial words, passported from oral conversation, mass media and Internet discourses during the years 2000–2024, as well as partially older colloquialisms that were not recorded in Ukrainian normative lexicographic works. Methods. The article uses both general scientific methods – analysis, synthesis, deduction, induction, as well as special linguistic methods – descriptive, observational, continuous sampling, comparative, and others. Results. The main sources of the origin of new colloquial words are identified and considered. The main sources of the named units is the actual live colloquial speech, in which neologisms always arise. Also, former social dialecticisms (jargonisms and argotisms), colloquial or colloquial borrowings, individual author’s novelties derived from popular colloquialism act as sources of replenishment of new lexemes. It has been proven that the most actively replenishing the new colloquial lexicon are such types of jargonisms as: military, sociolectisms from the field of informatics and computerization, from automotive jargon, from youth sociolects. The thematic groups of colloquial neologisms have been identified and analyzed. The largest of them are the names of persons. The dominance of this group is due to the powerful effect of the anthropocentric tendency in the Ukrainian language of the 21st century. It is worth emphasizing that it was during the analyzed period that the creation of various feminatives among the nomen to denote persons became extremely active (one can even call this phenomenon a “feminative boom”). It is proven that a significant part of them are new colloquial units. For the most part, they are the names of professions, a certain type of occupation, activity, social status, etc. and are formed with the help of productive suffixes -k(a), -in(ya), -its(ya), -es(a). A number of thematic groups were also identified: the military sphere, medicine and health care, units for marking realities and concepts in the field of education and science, household nominations, names of actions and processes, nominations of various signs and qualities. A considerable array of new colloquial non-codified words (more than 200 units) was introduced into scientific circulation. Conclusion. Colloquial neologisms significantly supplement the lexical-semantic system of the Ukrainian language of the 21st century, especially enriching its emotional-expressive, figurative, characterizing means. It has been found that the main sources of colloquial neologisms are actual spoken speech, former social dialecticisms (jargonisms and argotisms), colloquial or colloquial borrowings, individual author’s words created for popular colloquialism. The main thematic groups of studied units are highlighted – names of persons, the military sphere, medicine and health care, units for marking realities and concepts in the field of education and science, everyday nominations, names of actions and processes, nominations of various signs and qualities. Information about the author: Oleksandr STYSHOV – DSc (Philol.), Prof., Borys Grinchenko Kyiv Metropolitan University (Ukraine). E-mail: o.styshov@kubg.edu.ua __________ REFERENCES • Dictionary of the Ukrainian language: in 20 vols. (2010–). Naukova dumka. https://sum20ua.com/ [in Ukrainian]. • Kyryliuk, O. L. (2023). Discourse of information war: linguistic-cognitive and psycholinguistic aspects [Abstract of the thesis of the Doctor of Philol. Drohobych Ivan Franko Pedagogical University [in Ukrainian]. • Selivanova, O. (2006). Modern linguistics: a terminological encyclopedia. Dovkillia-K [in Ukrainian]. • Taranenko, О. О. (2002). Colloquization, substandardization, and vulgarization as characteristic phenomena of the stylistics of the modern Ukrainian language (since the end of the 1980s). Movoznavstvo [Linguistics], 4–5, 33–39 [in Ukrainian]. • Taranenko, О. О. (2005). The principle of androcentrism in the language coordinate system and the modern gender movement. Movoznavstvo [Linguistics], 1, 3–25 [in Ukrainian]. • Zhaivoronok, V. V. (Ed.) (2012). Dictionary of the Ukrainian language. VTs “Prosvita” [in Ukrainian].